A Concise Glossary of the Genres of Eastern Orthodox Hymnography - Kolyada, Elena (Journal of the International Society for Orthodox Music, 2020)
The Glossary contains entries on most of the genres of Eastern Orthodox hymnography that are mentioned in the article by E. Kolyada “The Genre System of Early Russian Hymnography: the Main Stages and Principles of Its Formation” published in JISOCM, vol. 3. As an addendum to the article it gives the reader the key for orientation within the elaborate system of liturgical chants (five large branches with numerous offshoots) discussed in the text and included in the tables. The Glossary can also be used as a helpful separate reference resource for the complicated hymnographic terminology. Though concise, the Glossary includes the main corpus of Eastern Orthodox liturgical chants. Each entry provides their definition, etymology and place within the ceremony. The Glossary is intended for students of theological educational institutions, chanters, scholars and all those interested in the Orthodox liturgical tradition.